1997
DOI: 10.1111/j.1399-3054.1997.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of ambient levels of solar UV‐A and UV‐B radiation on growth of cucumber

Abstract: 1997, Inhibitory effects of ambient levels of solar UV-A and UV-B radiation on growth of cucumber. -Physiol. Plant, 100: 886-893.The influence of solar UV-A and UV-B radiation at Beltsville, Maryland, on growth and flavonoid content in four cultivars of Cucumis sativus L. (Ashley, Poinsett, Marketmore, and Salad Bush cucumber) was examined during the summers of 1994 and 1995, Plants were grown from seed in UV exclusion chambers consisting of UV-transmitting Plexiglas, lined with Llumar to exclude UV-A and UV-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 41 publications
10
73
0
2
Order By: Relevance
“…We observed a 38% reduction in total biomass production of A. sativa growing under near-ambient UV-B (Figure 1) which was mainly the result of the reduction in aboveground biomass. These results agree with other studies conducted at similar [2,7,8] and higher [10,11] latitudes. The reduction in biomass does not appear to be related to reductions in tiller or leaf production (data not shown) but rather reductions in leaf elongation (Figures 2a and 2b).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We observed a 38% reduction in total biomass production of A. sativa growing under near-ambient UV-B (Figure 1) which was mainly the result of the reduction in aboveground biomass. These results agree with other studies conducted at similar [2,7,8] and higher [10,11] latitudes. The reduction in biomass does not appear to be related to reductions in tiller or leaf production (data not shown) but rather reductions in leaf elongation (Figures 2a and 2b).…”
Section: Discussionsupporting
confidence: 83%
“…Plant responses to UV-B tend to be subtle and species-specific, especially when studies are conducted outside under realistic spectral regimes. Responses to elevated and ambient UV-B include increases in DNA-damage and antioxidant response [2], alterations in plant morphology and architecture [3,4], slight reductions in chlorophyll fluorescence parameters associated with photosystem II [PSII; 5,6] and lower biomass accumulation [7][8][9][10][11]. The most common response of field-grown plants to elevated and ambient levels of UV-B appears to be an increase in concentrations of UV-absorbing phenolics [1,12,13] that may ameliorate potentially damaging UV-B before it reaches sensitive chromophores [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…When the effect of ambient solar UV-B radiation was examined in mung bean, a decrease in the leaf area development, plant height and net photosynthesis was detected (Pal et al, 1997). Comparably, Krizek et al (1997) observed that the four tested cucumber cultivars had decreases of 25.0-28.6% in biomass, 21.2% in stem height and 25.9% in leaf area under ambient UV-B radiation. Cybulski and Peterjohn (1999) reported that short-lived herbs appeared to be much more sensitive to ambient solar radiation than other plants.…”
Section: Effect Of Uv-b Radiation On Plant Growth Development and Prmentioning
confidence: 83%
“…To provide PAR (800-1000 mm/m 2 /sec), the chamber was equipped with eight evenly spaced 1000-W metal halide UV-B lamps. While metal halide lamps do not deliver the exact spectral balance of outdoor PAR, they are often used in experiments involving UV-B exposure to provide the PAR required to ameliorate UV-B-induced injury through activation of repair enzymes (Krizek et al 1997).…”
Section: Methodsmentioning
confidence: 99%